Modern marvels Architectural wonders. Golden Gate Bridge ; St. Louis Arch (New York A&E Television Networks Marketed and distributed in the U.S. by New Video Group, 2007)
This program circles the globe to profile the world's most phenomenal architectural gems: Baseball Parks, the Egyptian Pyramids, the Eiffel Tower and much more!
Originally aired on the History Channel.
"Go behind the scenes of the world's most stunning and awe-inspiring masterpieces of design and function with MODERN MARVELS."
DVD.
Keywords: Engineering design; Gateway Arch (Saint Louis, Mo.); Saint Louis (Mo.) -- Buildings, structures, etc; Golden Gate Bridge (San Francisco, Calif.).; San Francisco (Calif.) -- History